2012
DOI: 10.1002/nme.3358
|View full text |Cite
|
Sign up to set email alerts
|

Associated computational plasticity schemes for nonassociated frictional materials

Abstract: A new methodology for computational plasticity of nonassociated frictional materials is presented. The new approach is inspired by the micromechanical origins of friction and results in a set of governing equations similar to those of standard associated plasticity. As such, procedures previously developed for associated plasticity are applicable with minor modification. This is illustrated by adaptation of the standard implicit scheme. Moreover, the governing equations can be cast in terms of a variational pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…When using structured finite element meshes with a non-associated flow rule, it has been observed that the failure surface tends to propagate along element boundaries [4]. This effect can also be seen in Figs.…”
Section: Influence Of Mesh Discretization In Srfeamentioning
confidence: 79%
See 1 more Smart Citation
“…When using structured finite element meshes with a non-associated flow rule, it has been observed that the failure surface tends to propagate along element boundaries [4]. This effect can also be seen in Figs.…”
Section: Influence Of Mesh Discretization In Srfeamentioning
confidence: 79%
“…Nordal [11]). This issue has also been studied extensively by Krabbenhoft et al [4,8]. The main problem with a non-associated flow rule is that the solution of the governing equations is not unique.…”
Section: Influence Of Flow Rule In Srfeamentioning
confidence: 96%
“…Krabbenhoft et al . also used this SOCP approach to approximate a non‐associated flow model by a convex one. In all of these primal approaches, a concept similar to the Sherman–Morrison–Woodbury formula is used to reduce the linear system to be solved .…”
Section: Primal Problem Of Incremental State Updatementioning
confidence: 99%
“…Although we consider only quasi-static problems here, the concepts developed have implications in dynamic analyses [3,11,23,26,55,56]. They are also relevant in the finite deformation case and in instances where convexity does not apply, because these can often be approached using a succession of convex subproblems [20,[57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Incremental formulations using SOCP for continuum and discrete modelling approaches which take into account non-associative behaviour have also been recently developed (Krabbenhoft et al, 2012). Even so, considering the different field of application, also in these cases crushing is not taken into account.…”
Section: Introductionmentioning
confidence: 99%